BS EN IEC 62841-4-6. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 4-6. Particular requirements for garden blowers, garden vacuums and garden blower/vacuums (18th June 2021) - British Standards Institution,
No abstract available